Pengaruh Pendapatan Usaha dan Biaya Operasional Terhadap Laba Bersih PT Putra Teknindo Inspection Pekanbaru - Iqbal Satria Ananda; Mariaty Ibrahim (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
The objective of this research is to ascertain how operating income and operating costs affect net profit. The technique in research is quantitative. Secondary data are used because they come from documents, information, and quarterly profit and loss report data from PT's financial reports for the years 2014 to 2021. Putra Teknindo Pekanbaru Review. The results of the data analysis, which includes the classical assumption test, linear regression analysis, hypothesis testing, and determination coefficient test, indicate that operating income has a positive and significant effect on net profit of t count (25784.599) > t table (2045 ), that operating costs have a negative and significant effect on net profit of t count (-19942.949) > ttable (-2045), and that the F test of business income and operating expenses on net income has a value of F count. (363113403.588) > F table (3.32) meaning that operating income and operational costs simultaneously have a significant effect on net profit